SYMBOLIC ECONOMIES: MONEY, NEOLIBERAL LAW AND NATIONAL POLITICS IN ARGENTINA. - Castagno, Pablo (Cultural Studies)
In this article, I examine Argentina's neoliberal reforms throughout the 1990s from a Marxist theoretical perspective, analysing how money, monetary policy and law constitute a fundamental mode of ideological regulation in neoliberal capitalism. Situating this analysis in the context of the capitalist crisis of the mid-1970s, the article discusses the politics of effacement that in Argentina's case paved the way for the use of monetary policy as a form of social control intended to embed the nation-state into global capitalism. Examining economic legislation, macroeconomic policies, political ideologies, consumer discourses and pension privatization, I analyse how the neoliberal monetary regime ideologically underpinned a whole state imaginary based on exchange rate parity with the US dollar. Further, I investigate the ideological function of money in symbolically reordering the relationships of workers and citizens to the state, capital and culture. The article concludes with an exploration of the political significance of the monetary collapse of the Argentine neoliberal reform in 2001-2002, comparing Argentina's crisis of hegemony with that of other states within global capitalism.